The railway children - Nesbit, E. (Edith) (Virago Press, 2017)
When their father is suddenly taken away, the children's lives change overnight. Unable to afford their London home, the family must move to a small cottage in the Yorkshire countryside. Hiding their sadness from their mother, Roberta, Peter and Phyllis roam the fields all day. Every morning they can be seen waving as the 9.15 train roars past, imagining that it will can carry their love to their father, wherever he may be. The trio become a familiar sight and their bravery and quick-thinking avert a railway disaster. There is a kind old gentleman passenger never fails to wave back - little do the children realise how much his friendship will mean to them, especially in solving the mystery to their father's disappearance.